Tuberculosis and Diabetes Mellitus Control and Care: A Rapid Situational Analysis for Planning a Coordinated Program Response - Grace Kathleen T. Serrano; Emmanuel S. Baja; Mary Ann D. Lansang; Marissa M. Alejandria; Nina Castillo-Carandang; Jill R. Itable (Philippine Institute for Development Studies (PIDS), 2014)
Tuberculosis (TB) remains one of the leading killers among bacterial diseases worldwide. In the Philippines, the prevalence of culture-positive TB is estimated to be 5 per 1000 and that for sputum smear-positive pulmonary TB is 2 per 1000 based on the 2007 National Prevalence Survey. In addition, the prevalence of metabolic syndrome among Filipinos is 5 percent or approximately 5 million people have diabetes (DM) in the Philippines. With the Philippines being endemic for TB, compounded by an upward trend of DM, there is a need to jointly address this tandem disease interaction. This study aims to mount a coordinated response to TB/DM with the following expectations: 1) improve the case detection rate for TB, 2) facilitate early management among patients, and 3) prevent a significant number of severe disease and deaths.Mixed methods are used to achieve the objectives including a systematic review and gray literature to estimate the magnitude of co-morbidity with TB and DM, records review specifically medical records on clinical charts of patients, cross-sectional survey on knowledge, attitudes, and practices of health care providers on TB/DM screening and care, focus group discussions comprising of program managers and technical advisors of the National Tuberculosis Program, and costing exercise on bidirectional screening of TB in diabetic patients and vice versa. Given the government's commitment to the nationwide control of TB, the underexplored frontier of TB among diabetic patients can be among the stretch goals toward increased case detection, management and prevention efforts. Likewise, the increasing prevalence of diabetes in the country and the associated risk of TB transmission in a TB-endemic population suggest the need for raising awareness on the need for TB screening. However, there is a body of programmatic and operational research questions to answer before an integrated approach to bidirectional screening can actually be implemented.
Keywords: 330; Philippines; diabetes mellitus; tuberculosis; coordinated program response